American Pain : how a young felon and his ring of doctors unleashed America's deadliest drug epidemic - Temple, John, 1969- (LP, an imprint of Rowman & Littlefield, 2015)
The king of the pill mills was American Pain, a mega-clinic that served as a prototype for the rest. From a pristine former bank building, doctors distributed massive quantities of oxycodone to hundreds of customers a day, mostly traffickers and addicts who came by the vanload. Inked muscle-heads ran security, greeting the morning rush of pill poppers with cries of Welcome to the dope hole! Strippers and high-priced hookers operated the pharmacy, counting out pills and stashing cash in garbage bags.